Factors Affecting Stock Returns in Detected and Non-Detected Earnings Manipulation Cases - Johan Novanto; Arthik Davianti (Jurnal Akuntansi, 2022)
This research aimed to show the difference in profitability ratios in affecting a company's stock return if earnings manipulation is detected or not detected. The profitability ratios used in this research are Earnings per Share, Net Profit Margin, and Return on Assets, with Firm Size as the control variable. There are 340 manufacturing company data listed on Indonesia Stock Exchange from 2016 to 2019 whose passed purposive sampling was used as this study data. This research applied the Beneish M-Score tool to detect earnings manipulation, which shows 276 companies detected and 64 companies not detected manipulation. The testing uses multiple regression to see the partial, simultaneous, and influence of independent variables on the stock return. The analysis shows that the profitability ratios of detected and non-detected affect stock return. Partially, the non-detected shows that EPS and ROA have a significant positive effect on stock return, while NPM is insignificant. While the partial test of detected manipulation shows that EPS and NPM have a significant positive effect, and ROA showed a significant negative effect. Both non-detected and detected earnings manipulation revealed an insignificant effect for the firm Size.